The 1st International Electronic Conference on Pharmaceutics 2020
DOI: 10.3390/iecp2020-08683
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Protein Precipitation for High-Loading Drug Delivery Systems for Immunotherapeutics

Abstract: Cancer is the second leading cause of death in the world and is often untreatable. Protein-based therapeutics, such as immunotherapeutics, show promising results in the fight against cancer, resulting in their market share increasing every year. Unfortunately, most protein-based therapeutics suffer from fast degradation in the blood, making effective treatment expensive, causing more off-target effects (due to the high doses necessary), and often require repeated injections to stay within the correct therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…88 Notably, the precipitation method that Liao et al 88 used to compare them was a one-step nanoprecipitation that did not precipitate catalase in NP form before mixing the catalase with the PLGA–PEG/acetone solution. Combined with the conclusion from Nelemans et al , 99 the acetone solution in PLGA may impact both the distribution and the activity of catalase.…”
Section: Nanoprecipitationmentioning
confidence: 67%
See 2 more Smart Citations
“…88 Notably, the precipitation method that Liao et al 88 used to compare them was a one-step nanoprecipitation that did not precipitate catalase in NP form before mixing the catalase with the PLGA–PEG/acetone solution. Combined with the conclusion from Nelemans et al , 99 the acetone solution in PLGA may impact both the distribution and the activity of catalase.…”
Section: Nanoprecipitationmentioning
confidence: 67%
“…Nelemans et al 99 recently optimised a drug delivery system to encapsulate BSA and amylase with PLGA. This study first showed that only acetonitrile could precipitate BSA with a homogeneous particle distribution while acetone and ethanol caused a heterogeneous particle distribution.…”
Section: Nanoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analyses were performed using GraphPad Prism (GraphPad Software Inc.) ACN to BSA solution under stirring (figure 2(A)). Previous studies demonstrated the fewest protein aggregates with smaller particle sizes and uniform distribution when ACN was utilised as the non-solvent compared with acetone and ethanol [38]. Thus, ACN was selected as the non-solvent for BSA.…”
Section: Discussionmentioning
confidence: 99%
“…We modified the protocol of Morales-Cruz et al [37] and Nelemans et al [38]. BSA was first precipitated into small spherical NPs.…”
Section: Protein Precipitation and Loadingmentioning
confidence: 99%